Die Schöne und das Biest - Vadim, Roger; Else, Jon; Sarandon, Susan; Kinski, Klaus; Huston, Anjelica
Beauty and her two sisters Marguerite and Georgette are living a life of poverty as their father’s merchant ships are lost at sea. When one of the ships arrives in port they think their lives will be transformed, but things do not go to plan. Instead of coming home with the family fortune, their father heads back home with bad news – and to make matters worse he somehow wanders onto the grounds of a castle owned by the Beast and meets with further trouble there. Because he has taken a white rose for Beauty, the Beast tells father that he must die or he must send one of his daughters in his place and then his life will be spared. Beauty decides to spare her father’s life by going to the Beast in his place. Will the Beast kill Beauty? [dudummesau.com]